ANALISIS PENGARUH PENGGUNAAN SISTEM MINIMUM QUANTITY LUBRICATION (MQL) DENGAN VARIASI FLUIDA LUBRICANT MINYAK NABATI TERHADAP KEAUSAN PAHAT DAN KEKASARAN PERMUKAAN BENDA KERJA - , ISTYAWAN PRIYAHAPSARA; , Dr. Eng. Herianto, S.T., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maching using coolant causing environmental problems. Improper coolant waste handling can damage surrounding environment. In Minimum Quantity Lubrication (MQL) there are lubrication that can reduce friction force between tool and working material thereby can reduce the rate of temperature rise, and can impove tool life. Ester oil is the common lubricant used in MQL environment, but still endanger the operator because it contain low acute poison (EPA, 2010). The purpose of this research is to analyse the use of vegetable oil lubricant as alternative MQL lubricant on tool life and surface roughness of the work material. This research using vegetable oils consisted of palm oil, coconut oil, soybean oi, and maize (corn) oil. Those vegetable oils were tested their physical properties to be compared with ester oil especially the kinematic viscosity and flash point properties. The test were using CNC Denford Cylone P machine, with SUMITOMO DCMT070204N-SU carbide as tool insert. The MQL nozzle were pointed on tool flank side. During machining, images of flank wear were (VB) captured. Turning process were done until flank wear reach 0.3 mm. According to the physical properties and turning test palm oil are choose as the best vegetable oil used as MQL lubricant because it is the most economical oil compared with other vegetable oils. Compared with dry, MQL palm oil produce longer life tool.Compared with wet and MQL ester oil, palm oil produce shorter life tool. Overall MQL technique producing better work marterial surface roughness compared with dry and wet.